Faunistic notes on hoverflies (Diptera: Syrphidae) in Slovenia - De Groot, Maarten (Acta entomologica slovenica (Ljubljana), 2004)
In the period of May till September 2003 hoverflies (Diptera, Syrphidae) were collected in several places across Slovenia. 70 species were found with 278 specimens in total. From these species 41 were new to Slovenia. Almost all species occur also in the neighbouring countries.
Keywords: Diptera; favna; insekti; muhe; Slovenia; Slovenija